(untitled) (Mother Language, 2025)
The swift expansion of the global gig economy has highlighted the essential need of English language skills for freelancers, especially in non-English-speaking nations such as Bangladesh. This quantitative study examines the impact of English proficiency on the success of Bangladeshi IT freelancers by analysing its link with employment options, communication efficacy, and revenue potential. A structured questionnaire was delivered to 104 intentionally selected IT freelancers through an online survey conducted via Google Forms. The questionnaire had Likert-scale items, and the gathered data were analysed with SPSS (version 26) to identify trends, frequencies, and connections. The f indings reveal that a substantial majority of participants see English ability as essential for obtaining lucrative projects, bolstering confidence in customer interactions, and mitigating challenges in proposal composition and auditory understanding. Statistical evidence indicates a robust correlation between advanced English proficiency and enhanced competitiveness on global freelancing platforms. Moreover, the majority of participants endorsed the establishment of specialised language training programs and championed government-backed measures to rectify skill deficiencies. Notwithstanding certain problems associated with language anxiety and restricted speaking fluency, the overall findings identify English as a crucial element in achieving success in freelancing. The study indicates that systematic enhancements in English language education and policy initiatives are crucial to empower Bangladeshi freelancers in the increasingly English-centric global digital economy. Mother Language, 2025; 9(1): 107-131